All Aboard! Providing Shipboard Technical Skills While Building Capacity in Ocean Observations - Lilian Krug; Fiona Beckman; Andrew Rees; Angelika Dummermuth; Cassandre Stymiest; Eva-Maria Brodte; Karen Wiltshire; Peter Croot; Sophie Seeyave (Oceanography, 2025)
Shipboard training equips early career ocean professionals (ECOPs) with the skills, knowledge, and confidence to tackle the challenges of marine research. Such training helps develop a workforce essential for implementing a truly global ocean observation system and advancing understanding of the ocean and its sustainable use. Working with other organizations and individuals, the Partnership for Observation of the Global Ocean (POGO) offers opportunities to ECOPs, mainly from developing countries, to join research cruises and acquire hands-on experience with real-world oceanographic work. These learning experiences can be organized either as one-on-one training on research cruises with spare berths or collective training on dedicated expeditions designed for larger groups of international students. This article introduces POGO’s shipboard training program by presenting examples from each of the modalities, and it explores the program’s long-term impacts and future directions.